(3GdUhU hGdZQGHs ((3GdbGgQIs (3hKjbIs, 2006)
(3eYQcI GdMjGI Hjf Gdbhj hGdVYja dG JfJgj hGdZQGH dG jJQc GdUHjGf jeQMhf(B..(3Hd jaJQSge hdG jaQMhf(B..(3JQj eG Md GdeTcdI?Cgj dgG Md?(B!(3Ce djS dgG Md?(B!(3MRfJ aGWeI hacQ NGdO CNhgG aCHOY CQhY acQI bO JfLM bO JaTd heG PfH GdUhU GdeScjf?(B!s
(3GdbUI(B--s (3GdfTjO(B--s (3dYHI GdMQha GdCHLOjI(B--s (3dYHI GdCTjGA(B--s (3dYHI GdJdhjfs
(3ef (B4 (3Edj (B9 (3SfhGJs
2
Keywords: (3GdZQGHs -- (3ehGO SeYjI hHUQjIs; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs